Long‐term geothermal warming reduced stocks of carbon but not nitrogen in a subarctic forest soil. (10th July 2021) - Peplau, Tino; Schroeder, Julia; Gregorich, Edward; Poeplau, Christopher
Abstract: Global warming is accelerating the decomposition of soil organic matter (SOM). When predicting the net SOM dynamics in response to warming, there are considerable uncertainties owing to experimental limitations. Long‐term in situ whole‐profile soil warming studies are particularly rare. This study used a long‐term, naturally occurring geothermal gradient in Yukon, Canada, to investigate the warming effects on SOM in a forest ecosystem. Soils were sampled along this thermosequence which exhibited warming of up to 7.7℃; samples were collected to a depth of 80 cm and analysed for soil organic carbon (SOC) and nitrogen (N) content, and estimates made of SOC stock and fractions. Potential litter decomposition rates as a function of soil temperature and depth were observed for a 1‐year period using buried teabags and temperature loggers. The SOC in the topsoil (0–20 cm) and subsoil (20–80 cm) responded similar to warming. A negative relationship was found between soil temperature and whole‐profile SOC stocks, with a total loss of 27% between the warmest and reference plots, and a relative loss of 3%℃ −1 . SOC losses were restricted to the particulate organic matter (POM) and dissolved organic carbon (DOC) fractions with net whole‐profile depletions. Losses in POM‐C accounted for the largest share of the total SOC losses. In contrast to SOC, N was not lost from the soil as a result of warming, but was redistributed with a relatively large accumulation in the silt and clay fraction (+40%). This suggests an immobilization of N by microbes building up in mineral‐associated organic matter. These results confirm that soil warming accelerates SOC turnover throughout the profile and C is lost in both the topsoil and subsoil. Since N stocks remained constant with warming, SOM stoichiometry changed considerably and this in turn could affect C cycling through changes in microbial metabolism. Abstract : A geothermal spring in a subarctic forest was used to quantify the effect of long‐term, whole‐profile soil warming on soil organic matter stocks and fractions in Yukon, Canada. Along a soil temperature transect with 7.7℃ temperature increase, soil organic carbon stocks were reduced by up to 27%, while nitrogen stocks remained stable. The fractionation of soil organic matter revealed that most soil organic carbon was lost from the particulate organic matter fraction. Although nitrogen stocks were constant along the gradient, a redistribution of nitrogen to the silt and clay fraction was observed.